A Comparative Analysis of English and Lamaholot (Eastern Adonara Dialect) Consonants - Awololon, Yohanes Octovianus L.; Erfiani, Ni Made Diana; Dewi, Ni Luh Desy Suari (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
This study presents a contrastive phonological analysis of consonant sounds between English and the Lamaholot language, focusing on the Adonara Timur dialect spoken in Desa Riawale. The study aims to examine the articulatory and distributive differences in consonant phonemes and their implications for English pronunciation acquisition by Lamaholot speakers. Employing a comparative phonetic methodology, data were gathered through systematic linguistic observations and recordings of native speakers. Findings indicate that several English fricatives (/v/, /Î¸/, /Ã°/, /Êƒ/, /Ê’/) and affricates (/Ê§/, /Ê¤/) are absent from the Lamaholot consonant inventory, posing potential challenges for learners in accurately pronouncing English. Meanwhile, common consonants such as bilabial stops and nasals exhibit varying distribution patterns across both languages. The bilingual and multilingual competence of Lamaholot speakers appears to mitigate some pronunciation difficulties. Pedagogical implications include recommending phonetic and dual-language instructional approaches, supplemented by audiolingual techniques, to effectively address learnersâ€™ specific phonological challenges. This study enriches applied linguistics by offering targeted strategies for second language teaching tailored to speakers of minority indigenous languages.